A89 THE IBD SYMPTOM INVENTORY: MEASUREMENT CHARACTERISTICS AND VALIDITY IN A CLINIC SAMPLE. (1st March 2018) - Sexton, K; Walker, J R; Targownik, L E; Graff, L A; Haviva, C; Beatie, B; Petty, S K; Bernstein, M T; Singh, H; Miller, N; Bernstein, C N
Abstract: Background: Most measures of IBD symptoms are clinician administered, and existing self-report measures suffer from narrow breadth, inadequate measurement properties, or burdensome length. The IBD Symptoms Inventory (IBDSI) was developed to assess a broader range of patient-reported IBD symptoms. Aims: To evaluate the measurement properties of a new self-report measure of IBD symptoms. Methods: Consecutive IBD patients attending an outpatient GI clinic were invited to participate while waiting for their appointment. Participants completed a survey which included the IBDSI, the IBD Questionnaire (Guyatt et al., 1989), and the Manitoba IBD Index (Clara et al., 2009). The IBDSI was developed by adapting symptom items from existing clinician-rated or diary-format symptom inventories; following factor analytic work, 35 items were retained assessing symptoms on 5 subscales: bowel symptoms, abdominal discomfort, fatigue, bowel complications, and systemic complications. As part of standard care, participants were administered the Harvey Bradshaw Index for Crohn's disease (HBI; Harvey & Bradshaw, 1980) or the Powell-Tuck Index for ulcerative colitis (PTI; Powell-Tuck et al., 1978) by a clinical nurse specialist with extensive experience in IBD. A gastroenterologist completed a global assessment of disease activity on a 4-point Likert scale (0=inactive to 3=severely active symptoms). Results: 267 patients (58.1% female; CD n =142, UC n =125; ages 18–81 years, M =43.4, SD =14.6) provided informed consent and completed the surveys. The IBDSI showed excellent internal consistency (α=0.93 for the total score, 0.55–0.88 for subscale scores), correlated highly with low IBD-related quality of life on the IBDQ ( r =-.89), symptom frequency on the MIBDI ( r =.67), and clinician-rated global assessment ( r =.70). ROC analyses found that a score ≥ 24 (in CD) or ≥ 17 (in UC) showed excellent sensitivity and specificity for the HBI and PTI cut offs of ≥ 5 for active disease (AUC = .93 and .95), respectively. Conclusions: The IBDSI is a reliable and valid patient-reported measure of a broad range of common IBD symptoms. The IBDSI showed strong measurement properties, with a supported factor structure, very good internal consistency, evidence of convergent validity, and excellent sensitivity and specificity to clinician-rated measures assessing active disease, and is thus recommended for use in either clinic or research settings. A shorter version of the measure (24 items) with similar measurement characteristics is available. Use of the measure could allow clinicians to score and follow symptom reports as a means to quantify the impact of interventions. Kathryn Sexton is supported by a CAG/CIHR post-doctoral fellowship. Funding Agencies: CAG, CIHR